Deficits in Long-Term Vaccine Immunity Among Childhood Cancer Survivors Despite Revaccination Programs - Alexander Zadruzny; Eva Tiselius; Tiia Lepp; Teodora Aktas; Teghesti Tecleab; Samuel Hellman; Maja Jahnmatz; Anna Nilsson (Vaccines, 2025)
Background: Childhood cancer survivors (CCSs) often experience impaired humoral immunity because of cancer treatments that increase their susceptibility to vaccine-preventable diseases. This study aimed to assess the seroprevalence of tetanus and rubella antibodies in CCSs compared to healthy, age-matched controls. Additionally, we explored the impact of cancer treatments on vaccine-induced immunity, examined the extent of revaccination after treatment completion, and evaluated the effectiveness of revaccination on seroprevalence. Methods: This retrospective study included 180 CCSs previously treated at Astrid Lindgren Children’s Hospital, Stockholm, between March 2019 and January 2023. Patient data were retrieved from electronic medical records. Seroprevalence data for rubella and tetanus antibodies in the 15–19-year age group were also obtained from a national seroprevalence study conducted by the Public Health Agency of Sweden. Results: CCSs exhibited significantly lower seroprevalence for both tetanus (77.7% vs. 92.7%) and rubella (79.1% vs. 97.5%) compared to age-matched controls. Revaccination with DTP-containing vaccines was more frequently administered than with the MMR vaccine. Tetanus and rubella seroprevalence were the lowest in children who had received intense chemotherapy. Among those who were revaccinated with the DTP vaccine after intensive treatment, 81 out of 98 (82.6%) had tetanus IgG levels above the threshold, compared to 24 out of 48 (50%) unvaccinated CCSs. In contrast, among those revaccinated with MMR, 57 out of 73 (78.1%) had positive rubella IgG, compared to 53 out of 73 (72.6%) unvaccinated CCSs with rubella IgG levels above the cut-off. Conclusions: Our findings highlight that vaccines are underutilized in CCSs with a notable gap in immunity, particularly among those who have undergone intensive treatments. Unexpectedly, MMR revaccination did not significantly affect rubella immunity. Given the increasing number of CCSs, it is essential to better understand how to effectively restore vaccine immunity in this population.